2020
DOI: 10.1055/s-0041-1726138
|View full text |Cite
|
Sign up to set email alerts
|

An Ayurveda Gargle Regimen in Management of Radiotherapy-induced Oral Mucositis

Abstract: Background Radiotherapy-induced oral mucositis (RIOM) in patients with head and neck cancer may lead to significant morbidity. OM may result in erythema, ulceration, and pseudomembrane formation. The usual time of onset is second or third week of radiotherapy (RT), after the doses of 16 to 18 Gy. OM may cause severe pain, significant weight loss, increased resource use, interruption or discontinuation of the treatment, and added cost of supportive care. Materials and Methods Patients who underwent RT and chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…In continued patient centric efforts, the study conducted in this hospital revealed the statistically significant reduction in Radiation Induced Oral Mucositis during radiotherapy for HNSCC with an Ayurveda Gargle regimen and with the added advantage of lesser recurrence after follow up of three years [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In continued patient centric efforts, the study conducted in this hospital revealed the statistically significant reduction in Radiation Induced Oral Mucositis during radiotherapy for HNSCC with an Ayurveda Gargle regimen and with the added advantage of lesser recurrence after follow up of three years [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…After three years the data was again presented and discussed. Later the paper was published with three years follow up [ 11 ]. Thereafter, our Medical Director suggested a Randomized Controlled Trial for the Oral Mucositis.…”
Section: An Initiative Of Integrative Cancer Carementioning
confidence: 99%